Phacomatosis pigmentovascularis: a rare case report - Singh, Santosh K.; Pandey, Amit K.; Meena, Balavant S. (International Journal of Research in Dermatology, 2022)
Phacomatosis pigmentovascularis is a rare group of syndromes characterized by the co-existence of a vascular nevus and a pigmentary nevus with or without extracutaneous systemic involvement. The existing classifications of phacomatosis pigmentovascularis are based on phenotypic characteristics. We report a case of phacomatosis pigmentovascularis, with nevus flammeus, nevus anaemicus and dermal melanocytosis without extracutaneous manifestations. The molecular basis of phacomatosis pigmentovascularis is yet to be elucidated. Whether the various subtypes of phacomatosis pigmentovascularis are separate molecular entities or phenotypic variants of the same disease needs to be settled.